Ethical issues related to epilepsy care in the developing world. - Tan, Chong Tin; Avanzini, G. (Wiley, 2009)
There are three major issues of ethical concern related to epilepsy care in the developing world. First, is it ethical for a developing country to channel its limited resources from direct epilepsy care to research? The main considerations in addressing this question are the particular research questions to be addressed and whether such research will bring direct benefits to the local community. Second, in a country with limited resources, when does ignoring the high treatment gap become an ethical issue? This question is of particular concern when the community has enough resources to afford treatment for its poor, yet is not providing such care because of gross wastage and misallocation of the national resources. Third, do countries with plentiful resources have an ethical responsibility to help relieve the high epilepsy treatment gap of poor countries? Indeed, we believe that reasonable health care is a basic human right, and that human rights transcend national boundaries. Although health care is usually the responsibility of the nation-state, many modern states in the developing world are arbitrary creations of colonization. There is often a long process from the establishment of a political-legal state to a mature functional nation. During the long process of nation building, help from neighboring countries is often required.